PENGARUH KONSENTRASI PERASAN MENGKUDU (Morinda citrofilia Linn) TERHADAP PERTUMBUHAN Shygella disenteriae - Ariana, Diah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PENGARUH KONSENTRASI PERASAN MENGKUDU (Morinda citrofilia Linn) TERHADAP PERTUMBUHAN Shygella disenteriaeDiah Ariana, S.T, M.Kes.Diahariana0101@gmail.com D3 Analis Kesehatan UM SurabayaÂ AbstractMengkudu (Morinda citrofilia Linn) Indonesia is known as a medicinal plant that can treat a variety of diseases. This studyÂ  to determine the effect of noni juice concentration on the growth of Shigella dysenteriae, the bacteria that causes the disease shigellosis (bacillary dysentery). The design of this study used an experimental design to test laboratory, noni juice obtained by weighing 100g were still ripe noni fruit (puti yellowish color and texture is still hard) and washed, blender 100gr noni plus 100ml of sterile distilled water, filtered with sterile gauze and then Stril put in a test tube, back in autoclav sterilized for 15 minutes at a temperature of 1210C that noni juice is really sterile. Inhibition test with freshly made juice dilution method at concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.13%, 1.57% and 0.78%, followed planted in the media Muller Hinton Shigella to know whether it is growing or not growing, Statistical data analysis using Chisquer test on Î± = 0.05. The test results showed Î»2 Chisquer count> Î»2 table, then Ho is rejected. The results showed 12.5% of concentration - 100% can inhibit the growth of Shigella dysenteriae while the concentration of 0.78% - 6.25% solid not inhibit the growth of Shigella dysenteriae, so it can be concluded that the noni (Morinda citrofilia Linn) can inhibit the growth of Shigella dysenteriae and noni efficiently used for dysentery patients because of the concentration of 12.5% was able to inhibit the growth of Shygella dysenteriae. Keywords: Mengkudu (Morinda citrofilia Linn) , Shigella dysenteriae